Reducing the Symptomatology of Panic Disorder: The Effects of a Yoga Program Alone and in Combination with Cognitive-Behavioral Therapy - Vorkapic, Camila Ferreira; Rangé, Bernard (Frontiers in Psychiatry, 2014)
Introduction: Yoga is a holistic system of different mind body practices that can be used to improve mental and physical health. It has been shown to reduce perceived stress and anxiety as well as improve mood and quality of life. Research documenting the therapeutic benefits of yoga has grown progressively for the past decades. Objectives: The primary goal of this study was to investigate the effects of yoga in patients suffering from panic disorder. We aimed at observing the efficacy of yoga techniques on reducing the symptomatology of panic disorder, compared to a combined intervention of yoga and psychotherapy. Method: Twenty subjects previously diagnosed with panic disorder were selected. Subjects were randomly assigned to both experimental groups: Group 1 (G1-Yoga: 10 subjects) attended yoga classes and Group 2 (G2-CBT + Yoga: 10 subjects) participated in a combined intervention of yoga practice followed by a cognitive behavioral therapy session. Subjects were evaluated two times during the study: pre-test and post-test. Psychometric tools included the Beck Anxiety Inventory (BAI), Hamilton Anxiety Rating Scale (HAM-A), The Panic Beliefs Inventory (PBI) and Body Sensations Questionnaire (BSQ). Results: Statistical analysis showed significant reductions in anxiety levels associated with panic disorder, panic-related beliefs and panic-related body sensations both in G1 and G2. However, the combination of yoga and cognitive behavioral therapy (G2) showed even further reductions in all observed parameters (mean values). Conclusion: This study observed significant improvement in panic symptomatology following both the practice of yoga and the combination of yoga and psychotherapy. While contemplative techniques such as yoga promote a general change in dealing with private events, CBT teaches how to modify irrational beliefs and cognitive distortions. This indicates that the techniques might have complemented each other, increasing the intervention efficacy.